2008
DOI: 10.1007/s00520-008-0547-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the cultural health belief model influencing health behaviors and health-related quality of life between Latina and Asian-American breast cancer survivors

Abstract: This study adds to the existing literature in that no study has focused on cultural health beliefs and health behaviors between Latina and Asian-American BCS. Evidence that Latinas and Asian Americans varied in the patterns of cultural factors influencing health behaviors and HRQOL might lead to the development of culturally sensitive breast cancer interventions for promoting positive health behavior and ultimately increasing HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
77
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 35 publications
0
77
0
Order By: Relevance
“…In terms of physical QOL, one study conducted in Hawaii reported that Filipino women have worse outcomes in terms of nausea/vomiting and symptom count than do Japanese, Hawaiian, and Caucasian women [20]. However, compared with Hispanics in another study, Asian American women expressed fewer physical difficulties caused by breast cancer treatments [21]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of physical QOL, one study conducted in Hawaii reported that Filipino women have worse outcomes in terms of nausea/vomiting and symptom count than do Japanese, Hawaiian, and Caucasian women [20]. However, compared with Hispanics in another study, Asian American women expressed fewer physical difficulties caused by breast cancer treatments [21]. …”
Section: Resultsmentioning
confidence: 99%
“…Among a multi-ethnic sample, Filipino women had significantly lower emotional functioning than did Caucasian, Japanese, or Hawaiian women [20]. However, compared with Hispanics, Asian American women expressed less emotional distress [21]. Similarly, another quantitative study reported that, compared to Caucasians and African Americans, Asian Americans showed the second-lowest level of emotional well-being, while Hispanic women exhibited the lowest level [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AI/AN women from Alaska had higher screening rates than those living in the Southwest [Centers for Disease Control and Prevention (CDC) 2012 ; Schumacher et al 2008 ]. Hispanic women also report moderate screening rates, 70 %; compared to non-Hispanic women (Lim et al 2009 ;Lopez-Class et al 2011 ; Native American Cancer Research Corporation Native Americans and Cancer). The women from these other racial/ethnic groups are more likely to face cultural barriers to receiving screening, e.g.…”
Section: Screening Behaviormentioning
confidence: 92%
“…The desire for psychological support and quality of life exhibited the strongest correlation, particularly for "psychological well-being" (Kleeberg et al, 2005). Moreover, the doctor-patient relationship was indirectly correlated with emotional well-being (Lim et al, 2009). Self-efficacy in patient-physician communication was directly associated with Health-related Quality of life in Chinese-Americans (Lim et al, 2013).…”
mentioning
confidence: 88%